GSio: A programmatic interface for delivering Big Earth data-as-a-service. Issue 1 (22nd December 2017) - Larraondo, Pablo R.; Pringle, Sean; Guo, Jian; Antony, Joseph; Evans, Ben
Abstract: In this paper, we present GSio, a software system for serving geospatial raster or gridded Big Earth Data at scale. GSio allows different scientific communities to consume geospatial analysis ready data. It provides a generic interface to the data, which removes the need to interact with individual files, and can interoperate with existing geospatial collections hosted on data centres and public clouds. A distributed compute model is used to read and transform the data in parallel using a cluster of compute nodes for delivering data as a service to users. Several use cases are presented demonstrating different scenarios where this service has been used.